Modernization of Pedagogical Education: Motivational Context - Ogorodnova O.V.; Kukuev E.A.; Frolenkova A.L. (Психолого-педагогические исследования)
The article presents research results of dynamics for motivated sphere among Tyumen State University students. Participants took part in federal project for modernization of pedagogical education, which effectuates practical oriented motive of future teachers. There are 66 students in experiment and 62 students for control. They are 2 and 4 years students, future specialists in “Pedagogical education” and ‘Primary education”. To access motivational sphere among students the authors use method of express diagnosis for pedagogical motivation (U.A. Korelyakova), scale of self-evaluation of pedagogical and professional motivation (N.H. Phetinskaya), survey of motives for profession choice (A.B.Popova). Research proved that motivated sphere of students who participated in testing for practical orientated modules moved towards statistically important strengthen of professionally significant motives, internal and external types of motivation, formation of multi-directed motives. Authors depict the importance and possibility of targeted strategy for student motivation.